مفهوم الالتزام الإسلامي في المعارك الأدبية: دراسة لأعمال مصطفى صادق الرافعي ومحمود شاكر The Concept of Islamic Commitment in Literary Battles: A Study of the Works of Mustapha S. al-Rafi'i and Mahmud M. Shakir - (Abdel Nasir Osman Sobair), عبد الناصر صبير (At-Tajdid - Intellectual Refereed Journal, 2014)
يدرس هذا البحث مفهوم الالتزام الإسلامي في المعارك الأدبية من خلال النظر في أعمال كل من مصطفى صادق الرافعي ومحمود محمد شاكر وما خاضاه من معارك أدبية في مصر. وقد ناقش الباحث مفهوم الالتزام في الأدب، حيث وضح أن تحديد معنى الالتزام كما هو شائع اليوم بين النُّقاد يواجه ثلاث عقبات أساسية تتمثل في مشكلة معايير التقويم والتصنيف، والتعصب الإيديولوجي، والحجر على الإبداع الفكري والأدبي. وحاول الباحث بيان العلاقة بين مفهوم الالتزام الإسلامي في الأدب (بما هو يعني الالتزام بقيم الفضيلة الأخلاق) من ناحية والأسباب المختلفة للمعارك الأدبية، مبرزًا بذلك الرابطة الوثيقة بين مفهوم الالتزام وقضايا الفكر والثقافة عمومًا. وقد كان هذا البيان ضروريًّا لتحديد زاوية النظر ومنهجية التحليل للأعمال موضوع البحث في سياق المرحلة التاريخية التي شهدت تلك المعارك الأدبية، حيث كان الصراع بين فريقين أساسيين: فريق يدعو إلى الأصالة ويدافع عن القيم الثقافية والشخصية الحضارية للأمة الإسلامية، وفريق تغريبي يبشر بقيم الغرب وثقافته ومدافع عن حضارته من ناحية أخرى. وقد أوضح البحث أن إسهام محمود شاكر في تلك المعارك الأدبية تجلى بصورة في منافحته عن روح الأصالة والاتساق في شعر المتنبي ونقضه للصورة المتناقضة التي رسمها له طه حسين، كما أبرز أن إسهام الرافعي قد تجلى في بلورته لمفهوم الإعجاز القرآني ورفع رايته في مواجهة نزعة الشك المنهجي التي تزعمها كذلك طه حسين. الكلمات الأساسية: الأدب، الالتزام في الأدب، الالتزام الإسلامي، المعارك الأدبية، الأصالة، التغريب، التجديد، مصطفى صادق الرافعي، محمود محمد شاكر. _______________________________________________ This article looks into the concept of Islamic commitment in literary battles by examining the works of Mustafa ØÉdiq al-RÉfiÑÊ and Mahmud Muhammad Shakir and the literary battles in Egypt in which they were involved. Thus, the author discussed the concept of commitment in literature whereby he showed that the definition of the meaning of this concept as commonly used by critics is faced by three major difficulties: the problem of the criteria of evaluation and classification, ideological dogmatism, and the censuring of intellectual and literary creativity. The author also highlighted the relationship between Islamic commitment in literature (as implying commitment to virtue and moral values) and the different causes that led literary battles, thus demonstrating the strong connection between the concept of commitment and cultural and intellectual issues in general. This clarification was necessary in order to determine the perspective and methodology of looking at the works under investigation within the context of the period in which those literary battles took place. Two main camps were engaged in those battles: those who advocated authenticity and defended cultural values and identity of the Muslim ummah, and those westernized people who were promoting the values and culture of the West. The article has demonstrated that the contribution of Mahmud ShÉkir to the literary battles in question can best be seen in his defense of the originality and consistency of al-MutanabbÊ’s poetry as against the inconsistent picture drawn by Taha Hussein about him. As for al-RÉfiÑÊ’s contribution, it is mostly manifested in his elaboration and promotion of the concept of inimitability of the Qur’an in the face of the method of systematic doubt also advocated by Taha Hussein. Keywords: Literature, commitment in literature, Islamic commitment, literary battles, authenticity, westernization, innovation, Mustafa ØÉdiq al-RÉfiÑÊ, Mahmoud Muhammad ShÉkir.